Minahasa Culture, Family Support, Health Worker Support, Self-Efficacy, and Knowledge Associated with Self-Care Behavior among Hypertensive Patients: A Cross-Sectional Study - Ismail, Dina Dewi Sartika Lestari; Pelealu, Christina Yunitha; Supriati, Lilik (Chakra Brahmanda Lentera Institute, 2026)
Background: Hypertension is a leading cause of stroke and cardiovascular disease, and its high prevalence in Indonesia remains difficult to control. Evidence on how psychosocial and cultural factors, including Minahasa local culture, influence self-care is still limited. This study examined the effects of knowledge, self-efficacy, family support, health worker support, and Minahasa culture on self-care behavior among hypertensive patients in Southeast Minahasa Regency. Methods: A quantitative correlational cross-sectional study was conducted among 165 hypertensive patients recruited by consecutive purposive sampling from the outpatient clinic of a general hospital in Southeast Minahasa. Data were collected using validated questionnaires, and associations between predictors and self-care behavior were analyzed using multiple linear regression (p < 0.05). Results: Self-efficacy (β = 0.381; p < 0.001) and family support (β = 0.329; p < 0.001) had significant positive effects on self-care behavior. Knowledge (β = –0.009; p = 0.895), health worker support (β = –0.065; p = 0.643), and Minahasa culture (β = 0.127; p = 0.405) showed no significant direct effects. The model explained 34.7% of variance in self-care behavior (R² = 0.347). Conclusion: Self-efficacy and family support are the main determinants of self-care behavior, whereas knowledge, health worker support, and Minahasa culture do not exert significant direct effects. These findings indicate that local cultural values alone do not automatically improve self-care and may act indirectly through family and psychosocial pathways. Hypertension programs should prioritize strengthening self-efficacy and mobilizing family support, and future longitudinal studies should test culturally grounded, family-centered interventions